2014
DOI: 10.1111/ctr.12381
|View full text |Cite
|
Sign up to set email alerts
|

Everolimus with low‐dose tacrolimus in simultaneous pancreas and kidney transplantation

Abstract: The efficacy and safety of everolimus (EVR) in simultaneous pancreas and kidney transplantation (SPKT) is unclear. We retrospectively evaluated 25 consecutive SPKT recipients at our center from November 2011 to March 2013. All patients received dual induction (Thymoglobulin/basiliximab) and low-dose tacrolimus plus corticosteroids. Nine patients who received EVR were compared with 14 patients who received enteric-coated mycophenolate sodium (EC-MPS); two patients who received sirolimus were excluded from the a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
17
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(17 citation statements)
references
References 23 publications
0
17
0
Order By: Relevance
“…The mechanism of the antiviral effect of the TAC/mTOR immunosuppression regimen is likely twofold: via a reduction in the dose of tacrolimus and possibly through a direct action on viral replication by mTOR inhibition. In both this report and the renal/pancreas transplant studies previously discussed, the tacrolimus dose was reduced when used in combination with a mTOR inhibitor . It has been previously shown that tacrolimus‐based immunosuppression is an important factor in the emergence of BK viremia after renal transplantation .…”
Section: Discussionmentioning
confidence: 83%
See 3 more Smart Citations
“…The mechanism of the antiviral effect of the TAC/mTOR immunosuppression regimen is likely twofold: via a reduction in the dose of tacrolimus and possibly through a direct action on viral replication by mTOR inhibition. In both this report and the renal/pancreas transplant studies previously discussed, the tacrolimus dose was reduced when used in combination with a mTOR inhibitor . It has been previously shown that tacrolimus‐based immunosuppression is an important factor in the emergence of BK viremia after renal transplantation .…”
Section: Discussionmentioning
confidence: 83%
“…A long‐term study from the University of Miami randomized KP recipients at the time of transplantation between TAC‐sirolimus and TAC‐MMF and demonstrated equivalent patient and graft survivals at 10 years post‐transplantation. Another report from that institution similarly showed no difference in outcomes at 1 year between TAC‐everolimus and TAC‐MMF cohorts . Other reports have noted comparable surgical complication rates to tacrolimus‐based immunosuppression and excellent graft survivals .…”
Section: Discussionmentioning
confidence: 92%
See 2 more Smart Citations
“…There are limited reports on its use in clinical pancreas transplantation. 21,22 The influence of mTOR inhibition on IRI is contradictory. Mammalian target of rapamycin inhibition has been protective in IRI of the heart.…”
Section: Discussionmentioning
confidence: 99%